Polypyrrole/ionic liquid/Au nanoparticle counter-electrodes for dye-sensitized solar cells : improving charge-transfer resistance at the CE/electrolyte interface - Loguercio, Lara Fernandes (2019)
To provide a viable alternative for counter electrodes used in dye sensitized solar cells, polypyrrole (PPy) based films have been synthesized via electrochemical deposition in the presence of the ionic liquid 1-butyl-3-methylimidazolium bis-(trifluoromethanesulfonyl) imidate (NTf2) and incorporated with gold nanoparticles (Aunanop). The films were analyzed by SEM, UV-Vis-NIR, Raman, Electrochemical impedance spectroscopy, Cyclic voltammetry and Conductivity measurements. The presence of the ionic liquid is found to result in a more conductive film, to improve catalytic reduction of I3 − and the electrochemical reversibility of the electrode. In addition to increase conductivity, impedance spectroscopy has shown that incorporating Aunanop in the PPy/NTf2 film helps improving the interfacial charge transportation, the electrocatalytic properties and solar energy conversion efficiency. DSSCs assembled with PPy based CE presented nearly the same J-V characteristic parameters as observed from conventional Pt based device